Modulation of immunity by tryptophan microbial metabolites - Li, Siying (Frontiers in Nutrition, 2023)
Tryptophan(Trp) is an essential amino acid that can be metabolized via endogenous and exogenous pathways, including the Kynurenine Pathway, the 5-Hydroxyindole Pathway (also the Serotonin pathway), and the Microbial pathway. Of these, the Microbial Trp metabolic pathways in the gut have recently been extensively studied for their production of bioactive molecules. The gut microbiota plays an important role in host metabolism and immunity, and microbial Trp metabolites can influence the development and progression of various diseases, including inflammatory, cardiovascular diseases, neurological diseases, metabolic diseases, and cancer, by mediating the body's immunity. This review briefly outlines the crosstalk between gut microorganisms and Trp metabolism in the body, starting from the three metabolic pathways of Trp. The mechanisms by which microbial Trp metabolites act on organism immunity are summarized, and the potential implications for disease prevention and treatment are highlighted.